2019
DOI: 10.5489/cuaj.6248
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis for transrectal ultrasound-guided prostate needle biopsy: Compared efficacy of ciprofloxacin vs. the ciprofloxacin/fosfomycin tromethamine combination

Abstract: Introduction: Some authors advocate an increase in post-prostate needle biopsy (PNB) infections associated with emergent quinolone resistance in E. coli, urging re-evaluation of antibioprophylaxis. In this study, we compared rates of post-PNB urosepsis associated with two oral regimens of antibioprophylaxis: ciprofloxacin (CIP) vs. ciprofloxacin and fosfomycin tromethamine combination (CIP/FOS). Methods: This retrospective pre-post intervention study included all patients who underwent PNB in two Canadia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…One of them was carried out in the Republic of Korea, which revealed the clinical efficacy of a combined regimen of FM and FQ in reducing overall infectious complications [ 9 ]. The other study focused on the incidence of sepsis within 1 month after TRUSPB in Canada, which also showed that the use of FM and FQ together was more effective than FQ alone in decreasing sepsis [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of them was carried out in the Republic of Korea, which revealed the clinical efficacy of a combined regimen of FM and FQ in reducing overall infectious complications [ 9 ]. The other study focused on the incidence of sepsis within 1 month after TRUSPB in Canada, which also showed that the use of FM and FQ together was more effective than FQ alone in decreasing sepsis [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although recently the practice of TPPBx has become more common with its low rate of urinary tract infections and sepsis, the exercise of transrectal biopsy is still ongoing in different clinics and hospitals ( Pepe and Aragona, 2013 ; Pepe and Pennisi, 2022 ). During transrectal prostate biopsy, prophylactic antibiotics is a common practice in patients to reduce post-biopsy sepsis, and antibacterial prophylaxis is recommended in the European Association of Urology (EAU) guidelines ( Morin et al, 2020 ). Many reports mentioned the drugs’ effect in gut microbiome, especially antibiotics, which can alter the homeostasis of gut normal flora and impose an imbalance of bacteria communities.…”
Section: Discussionmentioning
confidence: 99%
“…It was conducted in Canada during our documentation period. 32 Although the Canadian study focused on the incidence of sepsis within 1 month after TRUSPB, our study dealt with the overall incidence of infectious complications, including sepsis, for the same period. Because of this difference, it is anticipated that our study may be applied to a much broader clinical spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Because both studies were conducted retrospectively, prospective randomized studies should be conducted in the future. 32 …”
Section: Discussionmentioning
confidence: 99%